Consumer centrism : an integrative review: BAM 25th Annual Conference, Building and Sustaining High Performance Organisations in a Challenging Environment - Davies, Mark Alexander; Manolis, C; Prince, Melvin; Windsor, R D (2011)
Keywords: dept.mkt; ⛔ No DOI found

A model of trust and compliance in franchise relationships - Davies, Mark A. P.; Lassar, Walfried; Manolis, Chris; Prince, Melvin; Winsor, Robert D. (Journal of Business Venturing, 2011)
Despite the danger of franchisee non-compliance as a severe impediment to overall franchise operation and performance, there is currently minimal understanding of the key factors that lead to these behaviors. Using a foundation of relational exchange theory, we construct and test a model that demonstrates how two distinct forms of trust, based upon perceptions of franchisor integrity and franchisor competence, are critical to explaining the roles that relational conflict and satisfaction play in influencing franchisee compliance. Implications of these findings are then demonstrated to have compelling relevance to the effective management of franchise systems. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Compliance; Conflict; Franchising; Reciprocity; Satisfaction; Trust; dept.mkt

Switching costs and ad agency-client relationship longevity: an exploratory study - Davies, Mark; Prince, Melvin (Services Marketing Quarterly, 2011)
A model of switching costs is applied to ad agency-client relationships using agency theory. Switching costs are comprised of set-up costs that create barriers to switching to new agencies and exit costs that are barriers to severing relationships with current agencies. Switching cost theory offers insights into why large clients can maintain agency relationships. A survey of American clients shows how client size is associated with set-up and exit costs. These relationships are explained through diversity and scope of services, the creative risk associated with major brands, and the need for more sophisticated monitoring, each acting as switching barriers, extending longevity. © Taylor & Francis Group, LLC.
Keywords: Account longevity; Client size; Switching costs; dept.mkt

Social Interaction and Employee Health - Forbus, Robert; Snyder, Jason (Journal of Business Management and Change, 2011)
With social interaction, quantity does not equal quality. Persons may have frequent negative social interactions with other persons, such that the interactions are socially undermining, rather than socially supportive. Rook (1984) used regression analysis to demonstrate how negative social interactions impact upon well-being outcomes more powerfully and more consistently than do positive social interactions. Building upon Rook’s work, the present research examines a workplace weight loss intervention and demonstrates the power of socially supportive communication in measures of weight loss and healthy lifestyle changes. Management implications are discussed.
Keywords: Social interaction; dept.mkt; employee health; weight-loss interventions; ⛔ No DOI found

Virtual identities from virtual environments - Prince, Melvin (Handbook of Research on Digital Media and Advertising: User Generated Content Consumption, 2011)
The creation of identities in immersive online digital environments has become commonplace in consumer behavior. Consumers frequently enter into socially networked, computer mediated environments (CME’s) as avatars. A user can design his or her avatar by choosing typologies of facial features, body types and clothing styles. The chapter concerns Avatar analysis as a system for generating and analyzing consumer information of practical value to marketers. Avatar analysis enhances understanding of brand perceptions and meanings, discovers new ways of positioning and differentiating brands, and provides insights for improving the effectiveness of brand communications. Using websites such as Second Life to draw avatars, consumer identity projections are elicited based on consumers’ perceptions and interpretations of their own digital figure drawings i.e., virtual social identities of consumers and brands. These identity projections disclose their real and ideal selves, brand-as-a-person, and imagery of a typical brand user.
Keywords: dept.mkt